Stress-Induced Belly Dancer’s Dyskinesia in A Young Woman: A Rare Case Report - Nadia Gabriella; Rocksy Fransisca V. Situmeang (Universitas Pelita Harapan, 2025)
Background: Belly dancer’s dyskinesia (BDD) is a movement disorder characterized by involuntary and slow writhing, rhythmic contractions of the abdomen. This rarely encountered phenomenon has not been sufficiently explored, with limited evidence regarding its exact pathophysiology, etiology, and treatment. We present a rare case of stress-induced BDD in a 30-year-old female. Case summary: A 30-year-old female presented with a 2-month history of involuntary abdominal movements that were sudden in onset, approximately lasting 5-10 minutes, with preserved consciousness. Her symptoms were initially precipitated by stress. However, they worsened within the past week during her menstrual period. Past medical history was significant for long-standing anxiety disorder and depression, for which she took vortioxetine 10mg/day, clonazepam 0.75mg/day, and lorazepam 0.5mg/day routinely. Upon examination, undulating and continuous movements of the abdominal wall were observed. A diagnosis of BDD was made and the patient was treated with an increased dose of clonazepam 1mg/day. Her symptoms significantly improved within three days. Discussion: Aside from an underlying psychogenic factor, our patient did not have other risk factors for BDD, such as exposure to neuroleptics or history of abdominal trauma. Although certain drugs have been reported to induce BDD, the medications she took have never been reported to cause this condition. Thus, it is most likely that her dyskinesia was stress-induced. Conclusion: Clinicians may not be familiar with BDD due to its infrequency, and the lack of standardized diagnostic and management strategies makes it challenging to diagnose and treat. Therefore, further research and exposure to BDD are imperative.